MEMBUKA PINTU TRANSFORMASI: PERAN INOVATIF AKUN BELAJAR.ID DALAM REVOLUSI DIGITAL SEKOLAH - Sutono, Sutono; Mulawarman, Widyamike Gede; Haeruddin, Haeruddin (Jurnal Pengabdian Kreativitas Pendidikan Mahakam (JPKPM), 2024)
This study investigates how East Kalimantan Province's schools can benefit from digital transformation through Belajar.id accounts. Analysis of account activation and utilization rates, as well as the effects of Google Workspace adoption and platform evaluations, is done using data from the belajar.id account Dashboard and Merdeka Mengajar Platform. This study employs a quantitative descriptive methodology, gathering data via document analysis and surveys. The findings indicate that while teachers and other education staff have a high degree of activation, there is a sizable disparity in student account activation. At all educational levels, Google Workspace is widely used, with some districts and towns having higher adoption rates than others. The bulk of accounts on the Merdeka Mengajar, There are still problems with using assessments on the site because it has to be enhanced. This study sheds light on the variables that affect students' use of educational technology and offers suggestions for making the most use of digital platforms to raise academic standards.